2020
DOI: 10.1101/2020.07.27.222836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting the endolysosomal host-SARS-CoV-2 interface by clinically licensed functional inhibitors of acid sphingomyelinase (FIASMA) including the antidepressant fluoxetine

Abstract: The Corona Virus Disease 2019 (COVID-19) pandemic caused by the Severe Acute Respiratory Syndrome Related Coronavirus 2 (SARS-CoV-2) is a global health emergency. As only very limited therapeutic options are clinically available, there is an urgent need for the rapid development of safe, effective, and globally available pharmaceuticals that inhibit SARS-CoV-2 entry and ameliorate COVID-19. In this study, we explored the use of small compounds acting on the homeostasis of the endolysosomal host-pathogen interf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 39 publications
5
58
0
1
Order By: Relevance
“…In summary, our data suggest the use of FIASMA medications such as fluoxetine, amitriptyline, ambroxol, anti-ceramide antibodies and neutral ceramidase for the prevention and treatment of coronavirus disease. These data were confirmed by an independent study also following the ASM/ceramide approach that demonstrated an inhibition of the infection of cultured epithelial cells with SARS-CoV-2 by the FIASMAs fluoxetine, amiodarone and imipramine in Calu-3 and Vero E6 cells [59]. As mechanisms, the authors describe a lack of acidification in acidic organelles and a change in cholesterol abundance.…”
Section: Preclinical Evidencementioning
confidence: 54%
“…In summary, our data suggest the use of FIASMA medications such as fluoxetine, amitriptyline, ambroxol, anti-ceramide antibodies and neutral ceramidase for the prevention and treatment of coronavirus disease. These data were confirmed by an independent study also following the ASM/ceramide approach that demonstrated an inhibition of the infection of cultured epithelial cells with SARS-CoV-2 by the FIASMAs fluoxetine, amiodarone and imipramine in Calu-3 and Vero E6 cells [59]. As mechanisms, the authors describe a lack of acidification in acidic organelles and a change in cholesterol abundance.…”
Section: Preclinical Evidencementioning
confidence: 54%
“…It is of major interest that fluoxetine, a widely used antidepressant drug, efficiently inhibited the entry and propagation of SARS-CoV-2 in the cell culture model without cytotoxic effects and also exerted potent antiviral activity against two currently circulating influenza A virus subtypes, an effect which was also observed upon treatment with the FIASMAs amiodarone and imipramine (178).…”
Section: Drug Repurposingmentioning
confidence: 99%
“…1,2,4,8 The unconventional responsibilities, demanding working conditions, and the ambiguity in the role of the police may result in job stress and burnout and have been established in earlier studies as a source of occupational stress among Indian police personnel. 9,10 The concern about being infected from the community and workplace may also be a potential source of fear among police personnel. 1 Furthermore, concerns about carrying the infection to the family members may also be a source of psychological distress.…”
mentioning
confidence: 99%